Pengaruh Terapi Singkat Berfokus Solusi (TSBS) untuk Mengurangi Stres Kerja dan Meningkatkan Kesejahteraan Psikologis Perawat - Yulyanti, Yulyanti; Yunita, Yunita; Kusuma Negara, Candra; Prawira, Ricky (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Work-related stress is a significant challenge faced by nurses, particularly in high-demand hospital environments, and it negatively impacts psychological well-being, job performance, and service quality. This study aimed to evaluate the effectiveness of Solution-Focused Brief Therapy (SFBT) in reducing work stress and enhancing the psychological well-being of nurses at Banjarmasin Regional Hospital. A quasi-experimental design with pre-test and post-test control groups was employed. Sixty nurses were selected through purposive sampling and divided into intervention (n = 30) and control (n = 30) groups. The intervention consisted of five online video-based SFBT sessions conducted over four weeks. Instruments included a work stress questionnaire and the Indonesian version of Ryff’s Psychological Well-Being Scale (RPWBS). Validity testing yielded r-values > 0.423, and reliability testing showed high internal consistency (Cronbach’s Alpha = 0.894 and 0.912). Data were analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test via SPSS version 25. Results revealed a significant reduction in work stress scores (mean: 71.4 to 53.2; p = 0.001) and a notable increase in psychological well-being (59.3 to 74.1; p = 0.000). Participants also reported feeling more confident, calm, and reflective. The study concludes that SFBT is an effective, practical, and adaptable psychological intervention suitable for institutional adoption in hospital settings.